Early Carboniferous Back‐Arc Rifting‐Related Magmatism in Southern Tibet: Implications for the History of the Lhasa Terrane Separation From Gondwana. Issue 10 (26th October 2020) - Wang, Xuhui; Lang, Xinghai; Tang, Juxing; Deng, Yulin; He, Qing; Xie, Fuwei; Li, Liang; Yin, Qing; Li, Zhijun; Li, Zhuang; Yang, Zongyao; Dong, Shuyi; et al.
Abstract: The Lhasa terrane is widely regarded as an integral unit that separated from Gondwana in the Carboniferous or late Triassic, but this terrane may more reasonably consist of two subterranes that separated from Gondwana at different times. Here, we describe newly identified early Carboniferous (355–344 Ma) basic and intermediate intrusive rocks in the Xiongcun area, southern Tibet. The basic rocks that yield negative whole‐rock ε Nd ( t ) values (−5.04 to −2.94) and zircon ε Hf ( t ) values (−9.2 to −1.7), combined with the chemical compositions, indicate that the magmas were derived by the partial melting of an enriched lithospheric mantle in a back‐arc extensional setting. The intermediate rocks yield ε Nd ( t ) and ε Hf ( t ) values of −5.78 to −5.36 and −9.2 to −4.5, respectively, which suggests that they were likely produced via crust‐mantle mixing. By combining our results with those of previous studies on the Lhasa terrane, we consider that a broad back‐arc rift system, including northern and southern branches, developed along the northern margin of Gondwana under the southward subduction of the Paleo‐Tethys oceanic lithosphere during the early Carboniferous. The northern branch evolved into the Sumdo Paleo‐Tethys Ocean, which led to the separation of the North Lhasa terrane from northern Gondwana during the late Carboniferous. The subsequent northward subduction of the Sumdo Paleo‐Tethys oceanic lithosphere beneath the North Lhasa terrane during the early to middle Permian may have triggered the southern branch to further evolve into the Neo‐Tethys Ocean and eventually may have resulted in the South Lhasa terrane separating from Gondwana. Key Points: The Lhasa terrane records early Carboniferous back‐arc rifting‐related magmatism The initial rifting of the Lhasa terrane from Gondwana began in the early Carboniferous The Lhasa terrane contains two subterranes separated from Gondwana at different times